Intubating Conditions Comparison, After Administration of Propofol with Muscle Relaxant and Profofol without Muscle Relaxant-An Observational Study - Parag Sabale1 , Pratibha Deshmukh2 , Swapnil Meshram3 , Nandkishor Bankar4 , Ashok Choudhary5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: General anaesthesia is a condition where generally neuromuscular blocking agents in theform depolarizing or non-depolarizing agents are used for intubation of trachea. A quest for a safer andsuitable intravenous induction agent has led to the development of Propofol, a 2, 6, di-isopropyl phenol aftera series of investigations. Propofol also reduces hypertension and tachycardia which occurs response duringintubation. Thus this technique protect against the potential adverse effects of tracheal intubation like intracranial, intraocular hypertension and tachycardia.Material and Method: 100 adult patients of American Society of Anaesthesia (ASA) grade I & II of boththe sexes belonging to the age group of 18-55 years, from various surgical specialties and undergoingsurgery under general anaesthesia were divided in to two groups of 50 each. In both the group intubationwas graded and scored according to ease of laryngoscopy, position of vocal cord, coughing, jaw relaxationand movement of limb. Score of 5 was classified as excellent, 6-10 good, 11-15 poor and 16-20 as bad. Totalscore of <=10 was considered as acceptable and score of >=10 as unacceptable.Results: Youngest patient was of 18 years in group I and 20 years in group II. Eldest patient was of 54 yearsin group I and 55 years in group II. Maximum number of patients were in 20-30 years of age 31 (62%) ingroup I and 23 (46%) in group II. Excellent intubating conditions were seen in 32 (64%) patients of groupI and 49 (98%) patients of group II. Before induction baseline readings of mean arterial pressure, systolicblood pressure (SBP), diastolic blood pressure (DBP), and pulse rate were noted in both the groups values.Similarly reading above parameters were just after induction, after intubation, one minute after intubation,two minute after intubation and 5 min after intubation. In both the groups slight decrease in all the parameterwere noted just after induction. In both the groups slight decrease in all parameters were noted just afterinduction .However slight increase in value of all the parameter were noted after intubation. Differencewhich was noted was not statistically significant. Also after 5 minute of intubation parameter in both groupswere approximately similar that of baseline (p>0.05).Conclusion: 2.5 mg/kg body weight of Propofol with adequate doses of opioids and inhalational agent canproduce acceptable intubating condition when compared with Propofol 2.5mg/kg along with succinylcholine.